Development of Competency Framework for Nigerian TVET Teachers in Tertiary TVET Institutions - Sern, Lai Chee; Mohammed Adamu, Hamisu; Mohd Salleh, & Kahirol (Journal of Technical Education and Training, 2019)
Competency framework is a tool that determines the needed competencies for individuals in order to curtail the challenges that are existing currently and to uphold sustainable development. From the educational perspective, the competencies of TVET teachers are important as they might affect the teachers’ implementation of tasks, career development and graduates’ quality. Therefore, this research attempted to develop a competency framework for TVET teachers in Nigerian TVET tertiary institutions based on the Malaysian Human Resource Practitioners Development (MHRDP) Competency Model. The study adopted a survey design and 427 TVET teachers were identified as targeted sample. A set of questionnaire was developed based on the MHRDP Competency Model (α=0.61). A total of 218 questionnaires were distributed to five TVET tertiary institutions using stratified sampling technique and 205 questionnaires were successfully returned. Exploratory Factor Analysis was used to analyse the data. The findings revealed that 19 elements of competency were significantly relevant to Nigerian TVET teachers who work at tertiary institutions. The proposed competency framework is beneficial to be used as a guideline for the Nigerian TVET institutions and policy makers to plan the competency training and retraining courses for TVET teachers and staff development.